Meningkatkan Keterampilan Berpikir Kritis Melalui Penerapan Strategi Pembelajaran Inkuiri pada Mata Pelajaran Pendidikan Agama Kristen di Kelas X-7 SMA Negeri 1 Manado - Situmorang, Yehezkiel; Munthe, Horasman Perdemunta; Emor, Yefta Harni (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this study is to measure student’s critical thinking abilities ini the learning of christian Religious Education and to identify how inquiry-based learning strategies enchance student’s critical thinking abilities in the subject of Christian Religious Education in Class X-7 of SMA Negeri 1 Manado. The method used in this study in Classroom Action Research following Sthepen Kemmis Svheme with 2 cycles consisting of planning, implementation, observation, and reflection for each cycle. Data collection instruments include critical thinking skill test, classroom observation and documentation. Data analysis techniques used are quantitative data analysis and qualitative data analysis. From the pre-cycle data, it was found that student’s interpretative skills were at 66,8%, which increased to 73,9% in cycle I and futher increased to 88,9% in cycle II. For analitical skills, the pre-cyle precentage was 10,9%, which increased to 73,9% in cyle I, and the reached 88,9% in cycle II. The evaluation ability in the pre-cycle was found to 10,9%, while in cycle I it increased to 73,9% and then increased again in cycle II to 88,9%. Student’s inference abilities in the pre-cycle were at 10,9%, then increased to 73,9% in cycle I, and further increased to 88,9% in cycle II. For this research data, it can be concluded that 1) there is a significant improvement in term sif interpretative, analytical, evaluative, and inference abilities. 2) Inquiry-based learning strategies have proven to be effective in enhancing critical thinking skills in the subject of christian Religious Education in class X-7 of SMA Negeri 1 Manado.